Hormonal pleiotropy and the juvenile hormone regulation of Drosophila development and life history. - Flatt, T.; Tu, M.P.; Tatar, M. (BioEssays, 2005)
Understanding how traits are integrated at the organismal level remains a fundamental problem at the interface of developmental and evolutionary biology. Hormones, regulatory signaling molecules that coordinate multiple developmental and physiological processes, are major determinants underlying phenotypic integration. The probably best example for this is the lipid-like juvenile hormone (JH) in insects. Here we review the manifold effects of JH, the most versatile animal hormone, with an emphasis on the fruit fly Drosophila melanogaster, an organism amenable to both genetics and endocrinology. JH affects a remarkable number of processes and traits in Drosophila development and life history, including metamorphosis, behavior, reproduction, diapause, stress resistance and aging. While many molecular details underlying JH signaling remain unknown, we argue that studying "hormonal pleiotropy" offers intriguing insights into phenotypic integration and the mechanisms underlying life history evolution. In particular, we illustrate the role of JH as a key mediator of life history trade-offs.